The influence of time reaction to characteristic of methyl ester sulfonate from seed oil ketapang - Poedji Loekitowati Hariani; Fahma Riyanti; Ahyati Fadilah (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2016)
The aim of the present work was to The Preparation of Methyl Ester Sulfonate From Ketapang Seed Oil As Surfactant. The research is to determine the optimum condition synthesis of methyl ester sulfonate surfactant with reaction time variations (3.5; 4.0; 4.5; 5.0; 5.5 hours). The methyl ester from ketapang seed oil were analysis by GC-MS and identified methyl ester sulfonate by using FTIR spectroscopy. The methyl ester from ketapang seed oil showed containing of methyl palmitoleic, methyl linoleic, methyl palmitate, methyl stearate, methyl oleic, methyl palmitolenat and methyl eicosenoate. The optimum condition of methyl ester sulfonate at reaction time 4.5 hours with the mass of methyl ester sulfonate 34,85 g. For the FTIR spectra of sulfonate group is indicated  by shifting of wave number at 1118.71cm-1 until 1029.1 cm-1. The characteristics of methyl ester sulfonate at the optimum reaction time have emulsion stability 71.684%, density 0.8714 g/mL, surface tension 36.232 dyne/cm, and maximum absorbance 1.428 at the maximum wavelength 660 nm. Keywords: Surfactant, methyl ester sulfonate, time reaction, ketapang seed oil